Motivation and Commitment to Sports Practice During the Lockdown Caused by Covid-19 - Leyton-Román, Marta; de la Vega, Ricardo; Jiménez-Castuera, Ruth (Frontiers in Psychology, 2021)
The state of alarm declared on March 14, 2020 caused changes in the population in relation to the habits of physical activity and sports practice. This study analyzed what motivational variables predicted the self-efficacy and commitment to sports practice, as well as the differences according to gender, during lockdown and the progressive de-escalation caused by COVID-19, using the Theory of Self-determination as a theoretical framework. The study sample was conformed of 179 subjects (90 men and 89 women) between 18 and 65 years of age (M = 28.64; SD = 10.28). The Behavioral Regulation in Sport Questionnaire (BRSQ), the Psychological Need Satisfaction in Exercise Scale (PNSE), the Physical Activity Self-Efficacy scale and the Sport Commitment scale, were applied. The most relevant results have showed significant differences in favor of the male gender in terms of levels of controlled motivation and amotivation, as well as higher levels of self-efficacy and basic psychological need of autonomy. Furthermore, the regression analysis has revealed that self-efficacy and current commitment to sports practice were explained by a variance of 57% and 64%, respectively, due to autonomous motivation and the basic psychological need of competence. Therefore, the basic psychological need of competence should be fostered in order to increase the levels of self-determined motivation, self-efficacy and commitment to sports practice of the population.